Interfacial tension of oil/water emulsions with mixed non-ionic surfactants: comparison between experiments and molecular simulations. Issue 6 (11th January 2016) - Posocco, P.; Perazzo, A.; Preziosi, V.; Laurini, E.; Pricl, S.; Guido, S.
Abstract : Smaller Span molecules occupy the free spaces between bulkier Tween molecules thus lowering interfacial tension as compared to those obtained for single surfactant systems. Abstract : Stable oil/water emulsions are usually obtained by using mixtures of different surfactants. Such systems display synergistic interface stabilizing effects, which have not been fully elucidated yet. Moreover, in many applications surfactants are added at concentrations well above their critical micellar concentration (CMC), and this regime has not been thoroughly explored in the literature as well. Here, we investigate oil/water emulsions through oil/water interfacial tension using two common non-ionic surfactants, Tween 80 and Span 20, in the concentration range C (0.3–1 wt%) well above their respective CMCs. Mesoscale molecular simulations coupled interfacial tensiometry experiments to characterise these interfaces at a molecular level. Interfacial tension γ was measured by a pendant drop technique. Coarse-grained calculations provided a microscopic view of the interface at the molecular level ( i.e. surfactant arrangement, interface thickness), and were employed to extend the study to those surfactant concentrations where experiments could hardly provide reliable data, if any. We found a significant synergistic effect between Tween 80 and Span 20, with low molecular weight Span molecules occupying free spaces between the much larger, bulky Tween compounds. The surfactant intermolecular interactions could be associated to a striking decrease of interfacial tension in going from pure surfactants to a mixture at the same total weight concentration. Furthermore, the interface was found to exhibit a spatial inhomogeneity with a "patch-like" organisation, reminiscent of microphase separation. Our results show that the proposed, combined experimental/ in silico approach provides relevant insights for several industrial applications, such as emulsion stability and oil spill remediation.